FISHING GROUND, CACTH COMPOSITION, HOOK RATE AND LENGTH DISTRIBUTION OF BILLFISHES CAUGHT BY TUNA LONG LINE IN INDIAN OCEAN - Fathur Rochman; Abram Barata; Budi Nugraha (Research Center for Fisheries, 2013)
Billfishes area by cacth of tuna long line vessels in Indian Ocean. Billfish are consist of swordfish Xiphias gladius, black marlin Makaira indica, indo facific blue marlin Makaira mazara, stripe marlin Tetrapturus audax, indo facific sailfish Istiophorus platypterus and shortbill spearfish Tetrapturus angustirostris. Besides that, billfishes also have important economic value compared with tuna as an exsported species such as swordfish and marlin. To optimize the catch of billfishes in Indian Ocean, data and information of potential fishing ground, size and catch composition of this species are needed. The billfishes cacth composition collected in 2011 were dominated by 45% swordfish, 20% black marlin, 19% blue marlin,9% short bill spearfish, 6% sailfish and 1%stripe marlin. The billfishes size range which were caught between 60 - 280 cm LJFL (Lower Jaw Fork Length). The sword fish average length was 150 cm, blue marlin 197 cm, black Marlin 189 cm, sailfish 150cm ,short bill spearfish 144 cm and stripe marlin159 cm. From this observation, it was found that most of billfishes caught were in mature.